Effects of Exercise on Low Density Lipoprotein Receptor Related Protein 5 Gene Expression in Patients With Postmenopausal Osteoporosis - Gamze KILIÇ; Didem DAYANGAÇ ERDEN; Özlem EROL; Erkan KILIÇ; Murat KARA; Hayat ERDEM YURTER; Ayşen AKINCI (Archives of Rheumatology, 2016)
Objectives: This study aims to investigate the effects of aerobic exercise on low density lipoprotein receptor related protein 5 (LRP5) gene messenger ribonucleic acid expression and evaluate the relationship between the clinical parameters and gene expression in patients with postmenopausal osteoporosis (OP). Patients and methods: Seven patients with postmenopausal OP (mean age 60.0±5.3 years; range 51 to 66 years) were included in the study. An exercise protocol/program consisting of treadmill exercising for 30 minutes three days a week for six weeks was performed at a moderate intensity. LRP5 gene expression levels were evaluated before the onset of the exercise program and then four hours after the end of the first session and 12th (fourth week) and 18th (sixth week) sessions of exercise. Results: Our results demonstrated variable changes in the LRP5 gene expression after the aerobic exercise sessions. Excluding one patient, the LRP5 gene expression levels showed a slight tendency to increase. In spite of this tendency, gene expression differences during the exercise sessions were not significant. Conclusion: Our results suggest that interindividual variations of LRP5 gene expression exist after moderate intensity aerobic exercises in patients with postmenopausal OP. Despite of this variability, LRP5 gene expression levels increased slightly, except in peripheral blood in one patient. Future studies with larger sample sizes and different sampling time/tissues are required to shed more light on the impact of exercise at molecular level in OP.